Biomimicry of ruminant digestion strategies for accelerating lignocellulose bioconversion in anaerobic digestion. Issue 12 (December 2022) - Bhujbal, Sachin Krushna; Ghosh, Pooja; Vijay, Virendra Kumar; Singh, Lakhveer
Abstract : Biomimicking ruminant digestion strategies (RDSs) into anaerobic digestion (AD) enables efficient bioconversion of lignocellulosic biomass. Understanding RDSs is essential to translate their features into designing and developing bioprocesses and bioreactors. Here, we discuss insights into recently developed bioinspired bioprocesses, bioreactors, and future AD systems based on RDSs.